2006
DOI: 10.1097/01.pas.0000194296.74097.87
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Nonneoplastic Pathology in Tumor Nephrectomy Specimens

Abstract: Pathologic changes in nonneoplastic renal parenchyma of nephrectomy specimens for renal tumors and the significance of these changes with regard to the outcome of contralateral kidney function have not been studied previously. We examined the nonneoplastic renal parenchymal changes in 110 consecutive tumor nephrectomy specimens, and we correlated our findings with patients' clinical information. The material was examined for the presence of any glomerular, tubulointerstitial, or vascular pathology. In our anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 19 publications
7
92
1
7
Order By: Relevance
“…These findings reinforce the necessity of non-neoplastic kidney assessment in cancer nephrectomies. 47,48 We compared global glomerulosclerosis, interstitial fibrosis/tubular atrophy, arteriolar hyalinosis, and arteriosclerosis in the surgical hematopoietic cell transplant group with non-transplant patients with renal cell carcinoma under 55 years of age (otherwise unmatched). Global glomerulosclerosis was greater in the hematopoietic cell transplant group (average 26, or 25% excluding patient with obstruction).…”
Section: Discussionmentioning
confidence: 99%
“…These findings reinforce the necessity of non-neoplastic kidney assessment in cancer nephrectomies. 47,48 We compared global glomerulosclerosis, interstitial fibrosis/tubular atrophy, arteriolar hyalinosis, and arteriosclerosis in the surgical hematopoietic cell transplant group with non-transplant patients with renal cell carcinoma under 55 years of age (otherwise unmatched). Global glomerulosclerosis was greater in the hematopoietic cell transplant group (average 26, or 25% excluding patient with obstruction).…”
Section: Discussionmentioning
confidence: 99%
“…1 Recent reports have highlighted the utility and value of diagnosing nonneoplastic renal disease in the tumor-free portion of the nephrectomy or partial nephrectomy specimen. [2][3][4] Studies of radical nephrectomy with long-term follow-up have demonstrated significant decline in renal function in 13% to 36% of patients. 1,5 Clinical parameters associated with postnephrectomy renal insufficiency include female sex, hypertension, diabetes, and preoperative proteinuria in univariate analysis, and preoperative serum creatinine level, hypertension, and preoperative proteinuria in multivariate analysis.…”
mentioning
confidence: 99%
“…Despite the focus of clinical studies mainly on demographics and laboratory factors, nonneoplastic histopathology is routinely available and intelligible in the majority of tumor nephrectomy specimens, with diagnostic tissue present in 92% to 98% of both partial and radical cases. 3,4,8 Two separate studies demonstrate the presence of diagnostic pathologic findings in as much as 90% 9 and more than 60% 4 of the kidneys where the nontumor portion from tumor nephrectomies were reviewed. The most common finding was diabetic nephropathy and vascular-related nephrosclerosis.…”
mentioning
confidence: 99%
“…Accordingly, clinical and pathological evidence has shown that this population of patients has a greater degree of underlying renal disease than previously appreciated. (Bijol et al, 2006;Kaplan et al, 1975) In fact, a retrospective cohort study of patients with small renal tumors by Huang et al showed that 26% of their patients with T1a RCC and normally functioning kidneys had pre-existing chronic kidney disease (CKD), defined as GFR <60 mL/min per 1·73 m 2 . The most common renal diseases found in patients with renal tumors are due to hypertension and diabetes.…”
Section: Renal Tumor Patients May Have Unrecognized Medical Renal Dismentioning
confidence: 99%
“…Bijol and colleagues reported that up to 60% of nephrectomy specimens show features of renal disease, most of which are due to changes from hypertension or diabetes. (Bijol et al, 2006) Other causes of renal disease include smoking, glomerulonephritis, cystic kidney diseases, congenital malformations, immune diseases, obstruction, and infection. Moreover, many of the risk factors that are implicated in the pathogenesis of renal disease overlap with the risk factors that contribute to renal cell carcinoma.…”
Section: Renal Tumor Patients May Have Unrecognized Medical Renal Dismentioning
confidence: 99%